(untitled) (Annals of Medical Research, 2026)
Aim: Hepatic hemangiomas (HHs) are the most common benign liver tumors, and giant lesions may cause symptoms or complications requiring intervention. Surgical resection carries significant morbidity, and minimally invasive alternatives such as transarterial embolization (TAE) have gained importance. This study aimed to evaluate the clinical and radiological outcomes of TAE with bleomycin–lipiodol emulsion for giant HHs and to examine the relationship between peripheral contrast filling and volumetric response. Materials and Methods: This retrospective, dual-center study included 41 patients who underwent TAE between January 2019 and June 2024. Indications for treatment were symptomatic lesions ≥5 cm, progressive growth of hemangiomas, or all lesions ≥10 cm. Contrast-enhanced MRI or CT was performed at 1, 3, 6, and 12 months post-treatment. Volumetric reduction ratio (VRR) and size reduction were calculated, and angiographic peripheral contrast filling was categorized into four groups (<25%, 25–49%, 50–74%, ³75%). Clinical outcomes, technical success, and complications were analyzed. Results: One patient was identified as a statistical outlier and excluded from the final analysis, which therefore comprised 40 patients (73 HHs). The mean baseline lesion diameter was 8.6 ± 0.5 cm, with a median volume of 178.3 cc (IQR 62.5–376.0). At 12 months, the mean VRR reached 75%, and 90% of patients achieved VRR ≥50%. Patients with ≥75% peripheral contrast filling had significantly greater volume reduction compared with lower filling groups (p < .001). Symptom resolution occurred in 93.5% of symptomatic patients. The overall complication rate was 25%, all of which were minor (SIR Grade A–B), and no major or persistent complications were observed. Conclusion: TAE with bleomycin–lipiodol emulsion is a safe and effective treatment for giant hepatic hemangiomas, providing substantial volume reduction and symptom relief. The degree of peripheral contrast filling may serve as a predictor of treatment success.